Decreased soluble Nogo-B in serum as a promising biomarker for Parkinson's disease - Liang, Hongming; Guo, Wenyuan; He, Honghu; Zhang, Hui; Ye, Qiongyu; Zhang, Qingxin; Liao, Jiajia; Shen, Yuefei; Wang, Jin; Xiao, Yousheng; Qin, Chao (Frontiers in Neuroscience, 2022)
Abstract Background: Recently, neurite outgrowth inhibitor-B (Nogo-B) receptor has been reported as a novel candidate gene of Parkinson’s disease (PD). Nogo-B receptor need to combine with soluble Nogo-B to exert its physiological function. However, little is known about the relationship between serum soluble Nogo-B and PD. Methods: Serum levels of sNogo-B and α-Synuclein (α-Syn) were measured in a cohort of 53 PD patients and 49 healthy controls with ELISA kit method. Results: Serum sNogo-B level is significantly lower in PD group than that in healthy controls and is negatively correlated with UPDRS-III score (p = 0.049), H&Y stage (p = 0.0108) as well as serum α-Syn level (p = 0.0001). Area under the curve (AUC) of serum sNogo-B in differentiating patients with PD from controls was 0.8010 while AUC of serum α-Syn was 0.930. Combining serum sNogo-B and α-Syn in differentiating patients with PD from HC presented higher discriminatory potential (AUC = 0.9534). Conclusion: Decreased serum sNogo-B may be a potential biomarker for PD. Lower Nogo-B level reflects worse motor function and disease progression of PD. Serum sNogo-B is of added value to serum α-Syn panel in distinguishing PD from controls. Future studies are needed to confirm in larger sample and different population. Keywords: Nogo-B receptor, Parkinson’s disease, α-Synuclein, biomarkers, NUS1.